Assessment of Fluoride Contamination of Groundwater at District Lower Dir: Implications for Public Health and Community Well-being - Sana Ullah; Muhammad Kashif Ashraf; Muhammad Bilal (Kurdish Studies, 2024)
Despite the widespread use of fluoride and its recognized benefits, it has been subjected to debate concerning its effectives and safety. On account of its critical role in dental health, significant public and scientific interest regarding fluoride has been sparked. The current study was carried out to assess fluoride concentration in groundwater of district Dir Lower, Khyber Pakhtunkhwa, Pakistan. During the present study a total number of 33 water samples were collected from different location of the study area. The results of the current study revealed that 21.212% of the total samples were fluoride contaminated while 78.788% were falling in permissible limits of world health organization (WHO), yet comprising of two samples having fluoride concentration below than WHO suggested lower permissible limits. Tehsil wise Munda was having the least (0%) fluoride contamination followed by tehsil Balambat, tehsil Samar Bagh and tehsil Adenzai (16.667%). Tehsil Timergara and tehsil Khall was having the highest fluoride contamination, both having 33.333% samples with fluoride contamination. It was also observed that there is no industrial and other such anthropogenic activities causing fluoride contamination, which suggests that, the fluoride contamination in some sampling sites may be due to geogenic orientation. Yellowing and cracking of teeth has been observed in local populaces of some areas, especially in local communities of riverine areas by the researchers as well. Therefore, it is suggested to employ different defluoridation techniques for fluoride removal, such as Gypsum addition and activated Alumina Treatment to make the water consumable.